Gene Expression Associated With Behaviour Manipulation in Wood Ants Infected With Larval Lancet Fluke, Dicrocoelium dendriticum - Chen‐Hua Li; Cameron P. Goater; James D. Wasmuth (Molecular Ecology, 2025)
Many ant species show dramatic shifts in behaviour when infected with parasites, but the molecular basis of these behavioural changes is not well understood. An example is the wood ant, Formica aserva , which serves as an intermediate host for the lancet liver fluke, Dicrocoelium dendriticum . Infected ants leave their nests during the cool hours of the day, ascend a flower and then attach themselves to a petal with their mandibles. Attached ants remain affixed to an inflorescence overnight, after which they detach, descend the plant and return to their nest. Unless eaten by a grazing mammal (the obligate next host), infected ants repeat this attach‐and‐detach cycle for the rest of the summer. We used transcriptomics to decipher the potential molecular mechanisms that underlie this reversible behaviour manipulation. Using naturally infected ants, we recreated the manipulation cycle in the laboratory and then evaluated messenger RNA from ant brains at four contrasting phases of manipulation. Among these phases, we found a total of 1349 transcripts differentially expressed between infected and uninfected ant brains. Many of these transcripts are involved in cell signalling pathways, including odorant, gustatory, vision, circadian rhythm and the production of biogenic monoamines and hormones. Metabolism, protein management and DNA repair functions might also play a role at different phases of manipulation. Our combined results are consistent with the idea that the mechanism(s) leading to the attach/detach/repeat sequence of behaviours of fluke‐infected ants is multifaceted, involving much more than temperature‐dependent contraction/relaxation of the mandibular muscles.